Persepsi Generasi Y Terhadap Kerajinan Tangan Daerah - Hazmanan Pasaribu; Chali Rafi; Khairawati Khairawati (JURNAL ILMIAH MANAJEMEN & BISNIS, 2017)
At this juncture, the growth of handicraft business in the world is quite rapidly which marked by the hard competition increasingly of handicraft products between the district of regions Aceh, therefore the handicraft entrepreneurs from Aceh must show a high competitiveness to other regional products through conduct a good marketing strategy. “Y” generation is an important consumer market segment in future due to the rapid growth of this generation and is also a high-income community. Consequently, the "Y" generation has attracted various research groups and scientific discipline attention. The aim of this research is to identify the perception of "Y" generation regarding the Lhokseumawe handicraft product. Through the quantitative approach via questionnaire this research found that: marginally, the perception of The generation “Y” at Lhokseumawe city to local handicraft products is still sufficient with low quality and the relatively expensive price. The purchasing of local handicraft products is only a gift or souvenir to introduce Aceh region and still not become a culture that shows the love of local products.